1987
DOI: 10.1128/jvi.61.12.3968-3976.1987
|View full text |Cite
|
Sign up to set email alerts
|

Sequence and translation of the murine coronavirus 5'-end genomic RNA reveals the N-terminal structure of the putative RNA polymerase

Abstract: A 28-kilodalton protein has been suggested to be the amino-terminal protein cleavage product of the putative coronavirus RNA polymerase (gene A) (M.R. Denison and S. Perlman, Virology 157:565-568, 1987). To elucidate the structure and mechanism of synthesis of this protein, the nucleotide sequence of the 5' 2.0 kilobases of the coronavirus mouse hepatitis virus strain JHM genome was determined. This sequence contains a single, long open reading frame and predicts a highly basic amino-terminal region. Cell-free… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
65
1

Year Published

1990
1990
1997
1997

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(71 citation statements)
references
References 51 publications
5
65
1
Order By: Relevance
“…A clone containing ~28, the 5'terminal portion of the putative polymerase gene, was constructed using published sequences and PCR technology (Soe et a/., 1987). To construct the p28 clone, a 5' primer (GCATAmGCAAAGATGG) and a 3' primer (TAAGG-TCGCCITAGTCTTC)…”
Section: Constructionmentioning
confidence: 99%
See 3 more Smart Citations
“…A clone containing ~28, the 5'terminal portion of the putative polymerase gene, was constructed using published sequences and PCR technology (Soe et a/., 1987). To construct the p28 clone, a 5' primer (GCATAmGCAAAGATGG) and a 3' primer (TAAGG-TCGCCITAGTCTTC)…”
Section: Constructionmentioning
confidence: 99%
“…Since p28 is normally cleaved from a large precursor, a T nucleotide was substituted for an A present in the original sequence (underlined above) in the 3' primer. This change introduced a termination codon into the construct at a position (amino acid 272) corresponding to a potential proteolytic cleavage site (Soe et al, 1987).…”
Section: Constructionmentioning
confidence: 99%
See 2 more Smart Citations
“…Denison and Perlman showed that in vitro translation of viral genomic RNA produced p28 and p220, and that production of p28 was inhibited by the addition of a proteinase inhibitor, zinc chloride (Denison and Perlman, 1986). Using an antiserum generated against a synthetic peptide representing a portion of p28, the p28 protein was detected in MHV-infected cells and shown to be the amino-terminal protein of the polymerase polyprotein (Denison and Perlman, 1987;Soe et al, 1987). Translation of RNAs representing the 5' end of the viral genome revealed that the PCP-1 domain was required for the autoproteolytic cleavage of p28 (Baker et al, 1989).…”
mentioning
confidence: 99%